Restructuring the sales force to improve the sales revenue of Green Development Sustainable Solutions, Inc. (GSSI) - Coruña, Michael A. (Animo Repository, 2020)
This Action Research paper is about increasing the sales revenue of Green Development Sustainable Solutions, Inc. by restructuring its sales team. The restructuring involved making the company’s technical people perform sales-related activities to win new contracts and to improve the overall sales performance of the company. This action research required me as the researcher to engage and collaborate with all stakeholders in identifying and addressing the main issue of the company: low sales outcomes. We followed the principles of the Action Research Cycle design by Cohglan and Brannick (2014). We completed two cycles of the different stages of action research: (1) construction, (2) planning action, (3) taking action, and (4) evaluating action. Further investigation led the researcher and collaborators to identify the underlying issues of the main issue. These were low manpower allocation for sales and marketing, low utilization of technical team, and redundancy of efforts. To ensure collaboration and trust, I gathered only a reasonable amount of data and applied action research tools such as different forms of inquiry. This research resulted in an increase in sales generated by the sales team after two cycles. The first cycle focused on involving the technical people in actual sales activities. The second cycle was about boosting morale and maintaining the motivation of the technical people through a rewards and incentive program. The changes and adjustments of the organization were minor, but the actual results yielded a huge improvement on the current sales revenue and process in terms of efficiency, sales coverage, and client engagement.